Strategi Direct Instruction dalam Pembelajaran Akidah Akhlak Pada Jenjang Pendidikan Madrasah Tsanawiyah) - Faiqatul Hikmah (JUMPA : Jurnal Manajemen Pendidikan, 2020)
The importance of the knowledge of Akidah Akhlak in human life, stimulates innovation and reform in the concept of teaching and learning in Akidah Akhlak subjects. The study analyzes and identifies Direct Instruction learning strategies in Akidah Akhlak subjects at the Madrasah Tsanawiyah level. This study is a review of Direct Instruction-based learning in Madrasah Aliyah. This study involved various sources related to the concept of Akidah Akhlak learning that took place at the Madrasah Tsanawiyah level based on the Direct Instruction strategy and Bandura's theory of behavior. This study resulted in a finding that the application of Direct Instruction (DI) in the Akidah Akhlak subject at the Madrasah Tsanawiyah level could be carried out in three stages, namely (a) explaining the objectives; (b) preparing students by arranging the subject of the previous lesson or giving a number of questions to students; (c) presentations and introductions, in which the teacher delivers presentations and material for Akidah Akhlak lessons that have been prepared in accordance with a predetermined curriculum; (d) perform guided exercises; and (e) ensure and ensure student understanding and provide feedback. Thus, the indicator for the application of Direct Instruction is that the learning process in Akidah Akhlak subjects will effectively lead students to declarative knowledge and procedural knowledge.